Analisis Manajemen Waktu Mahasiswa Aktivis IAIN Surakarta - Shokhib Rahmania; Eranda Wulan Agustina; Ammeisa Rahayuni (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
Time management is the process of timing to achieve specific goals. Some students who are involved in the organization forget about their responsibilities as students that must be completed. Therefore, this study aims to find out the motivation of activist students who have delaying their graduation. This study involved final-level students of IAIN Surakarta, especially the class of 2015-2016 with a sample of two informants. The data was collected through interviews and observations, so that this study used qualitative descriptive analysis techniques.Â  Based on the results of data, the reason why final-year students delay their graduation is because they are too fond and are comfortable in the organization. By organizing they can develop interests and talents that they cannot get outside the organization. By organizing they get experience and various positive things that they find in the organization only, get busy, entertainment until finally they neglect the final assignment of college as students.